Amino acid transfer free energies reveal thermodynamic driving forces in biomolecular condensate formation - Shiv Rekhi; Jeetain Mittal (Proceedings of the National Academy of Sciences, 2025)
The self-assembly of intrinsically disordered proteins into biomolecular condensates depends on their primary sequence, leading to sequence-dependent phase separation. Computational methods to study this behavior often rely on residue-level interaction potentials that estimate the propensity of amino acids to partition between the dilute and dense phases. While distribution coefficients would provide the most direct measure of these potentials, their unavailability has led to the use of proxies, most notably, hydropathy. However, recent studies have highlighted limitations in hydropathy-based models. Here, we address this fundamental gap by calculating the transfer free energies for amino acid side chain analogs moving from the dilute phase to the dense phase of biomolecular condensates. We find that, net transfer free energies arise from a balance between favorable protein-mediated and unfavorable water-mediated interactions, with a striking asymmetry between the contributions of positive and negatively charged residues. This asymmetry originates from the stronger solvation of negatively charged species, and extends to modified amino acids. We further demonstrate that the sequence features of the condensate-forming protein modulate these transfer free energies in a context-dependent, but qualitatively similar manner. These findings help explain nontrivial experimental trends and provide a foundation for interpreting the sequence-dependent driving forces underlying condensate formation.